Commercially available bone graft substitutes: the impact of origin and processing on graft functionality. (2nd October 2019) - Bow, Austin; Anderson, David E.; Dhar, Madhu
Abstract: Development of effective and cost-efficient bone tissue engineering grafts has been the key area of research for regenerative medicine, yet an ideal grafting material has remained elusive due in large part to the highly dynamic nature of bone. A wide array of materials, both natural and synthetic, have been implemented as potential candidates for commercially available products, yet the gold standard for grafting material still remains autogenous bone. We review currently commercially available bone graft materials and relevant graft characteristics that impact the effectiveness of tissue repair, emphasizing the advantages and disadvantages of materials based on composition and origin. Examined materials were selected through a web-based search for readily accessible and clinically applicable graft materials. Grafts were then categorized according to material source to examine advantages and disadvantages associated with allogenic, xenogeneic, synthetic materials. Lastly, the application of bioactive molecules onto these basal grafts is explored to illustrate the enhancement and regulative capacity of these additives on traditional osteobiologic materials.